Microfluidic Flexible Substrate Integrated Microstrip Antenna Sensor for Sensing of Moisture Content in Lubricating Oil - Lin Zhu; Wei Li; Xueyun Han; Yufeng Peng (International Journal of Antennas and Propagation)
In this paper, a flexible microstrip patch antenna sensor is proposed for monitoring of the moisture content of lubricating oil. The sensor identifies liquids having different effective dielectric constants by detecting changes in the resonance frequency. The proposed antenna comprises a radiation patch, a metal ground plane, and a PDMS substrate with microchannels. The microchannels are etched on the PDMS substrate. When the relative permittivity of the microfluidic channel is 1.8∼12.5, the operating frequency of the proposed antenna changes from 2.230 to 2.116 GHz, and the amplitude of the reflection coefficient is greater than −26.3 dB. The simulation and measurement results show that the proposed sensor can monitor the lubricating oil with different moisture contents, which can cause frequency separation of at least 20 MHz and achieve a good linear response. Therefore, the proposed sensor has the feasibility of monitoring the quality of lubricating oil.